Perumusan Rekomendasi Program Kerja Desa Digital di Desa Karuing, Kabupaten Katingan: Formulation of the Recommendation on Digital Village Work Plan in Karuing Village, Katingan District - Ariesta Lestari; Abertun Sagit Sahay; Felicia Sylviana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Digital village is the Indonesian government’s program to accelerate the development of a village and reduce the inequality in access to information between village and city. Advances in information technology have penetrated rural areas. It makes the implementation of digital village easier to implement. Karuing is a village in Katingan Regency, one of the villages that pointed to implementing a digital village in 2023. A meeting was held to inform the community about the implementation of Digital Village, followed by discussion and observation. The formulation of the work program was conducted at the end of 2022 through a focus group discussion with the village officials and the community. The results of the FGD were then analyzed using SWOT analysis, which became the basis of the formulation of the work program. The recommended work program covers the provision of ICT infrastructure in Karuing village, empowering the community to manage the ICT infrastructure and increasing the community’s digital literacy to maximize the implementation of the digital village. The main focus of the work program is the tourism attraction of Punggualas and the Eaglewood handicrafts that have high economic value.